2016
DOI: 10.1177/0733464816665204
|View full text |Cite
|
Sign up to set email alerts
|

Staff Empowerment Practices and CNA Retention: Findings From a Nationally Representative Nursing Home Culture Change Survey

Abstract: This article examines whether staff empowerment practices common to nursing home culture change are associated with certified nursing assistant (CNA) retention. Data from 2,034 nursing home administrators from a 2009/2010 national nursing home survey and ordered logistic regression were used. After adjustment for covariates, a greater staff empowerment practice score was positively associated with greater retention. Compared with the low empowerment category, nursing homes with scores in the medium category ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 36 publications
1
69
0
Order By: Relevance
“…The 162 occurrences were grouped into 11 different themes for the facilitators. The eleven "facilitator" themes as demonstrated in Table 2 and represented in Figure 1 included supportive leadership , capable and motivated employees [22,27,30,32,35,45,[49][50][51][52][53][54][55][56][57][58][59][60], positive organizational values [22][23][24]29,[31][32][33]48,51,53,54,57,[61][62][63][64], social support mechanisms, adequate job resources [32,38,45,47,54,55,[69][70][71], career/professional development [25,35,37,38,…”
Section: Most Impactful Themesmentioning
confidence: 99%
“…The 162 occurrences were grouped into 11 different themes for the facilitators. The eleven "facilitator" themes as demonstrated in Table 2 and represented in Figure 1 included supportive leadership , capable and motivated employees [22,27,30,32,35,45,[49][50][51][52][53][54][55][56][57][58][59][60], positive organizational values [22][23][24]29,[31][32][33]48,51,53,54,57,[61][62][63][64], social support mechanisms, adequate job resources [32,38,45,47,54,55,[69][70][71], career/professional development [25,35,37,38,…”
Section: Most Impactful Themesmentioning
confidence: 99%
“…The majority (n=25) were empirical research , mostly cross-sectional survey studies (Berridge et al 2018(Berridge et al , 2020Berta et al 2018;Bethell et al 2018 Fukuda et al 2018). Of these, one was a quasi-randomised comparative trial (Fukuda et al 2018).…”
Section: Paper Type/study Designmentioning
confidence: 99%
“…The overall design of work content is highlighted as being associated with resilience and retention (Yeatts et al 2018). How tasks are allocated will determine how much time staff spend with which residents, reported as a positive factor in staff retention by two papers (Castle 2018 andBerridge et al 2018). Nakanishi & Imai (2012) found that intention to leave was associated with the extent to which FCWs had discretion in how they used their skills and Braedley et al (2018) identified that having autonomy of tasks was of importance.…”
Section: Content Of Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that home care aides comprise the largest group of formal providers delivering services in the home, the published and gray literature has failed, for the most part, to acknowledge this workforce as a potential member of the team and has paid little attention to whether and how aides have been or could be incorporated into team‐based programs . Studies showed that incorporating certified nursing assistants (CNAs) into care teams has a direct positive effect on nursing home quality and an indirect effect by reducing CNA turnover . There has been no comparable research assessing the impact of home care aides as part of a team.…”
mentioning
confidence: 99%